A Survey Over The Effect Of Imaginary Exercises On Activation Of Shoulder Muscles - Khosro Khademi Kalantari; Nasrin Davoodi (Shahid Beheshti University of Medical Sciences, 2012)
Background and Aim: The present study was conducted to identify the effect of imaginary exercises on electrical activity of the shoulder muscles.Materials and Method: Twenty three healthy subjects (17 females and 6 males) with no history of shoulder injury participated in this quasi experimental study. Surface EMG was recorded by bipolar electrodes that were applied over the supraspinatus, infraspinatus, posterior deltoid, middle deltoid, anterior deltoid and pectoralis major. Subjects performed 6 imaginary exercises including imagination of flexion, extension, abduction, adduction, external rotation and internal rotation. The amount of RMS obtained in EMG while exercising was compared with the one obtained at rest.Results: Performing the imaginary exercises resulted in significant activation (P < 0.01) of the shoulder muscles. In the case of the supraspinatus muscle, a significant difference (P < 0.05) was found between exercise type and intensity of activation but no significant value was seen for infraspinatus muscle. In flexion, abduction, adduction & internal rotation imaginary exercises, correlation between muscles activation was also statistically significant (P<0.01).Conclusions: Imaginary exercises can be used as alternative means and the first step for shoulder muscles rehabilitation specialty when the movement of the joint is contradicted.